Pengaruh Persediaan, Penerapan Just In Time, dan Lean Accounting Terhadap Laba Bersih pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Priode 2022-2024 - Nabila Rama Hervianti; Maya Richmayati; Nur Isra Laili; Khadijah Khadijah; Hermaya Ompusunggu (Economic Reviews Journal, 2026)
This study aims to analyze the effect of inventory management, the implementation of Just In Time (JIT), and Lean Accounting on net profit in manufacturing companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research method used is a quantitative approach with secondary data obtained from companies’ financial statements. The sampling technique employed purposive sampling, resulting in 39 companies observed over three years, yielding 117 observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, along with classical assumption tests and hypothesis testing. The results indicate that partially, inventory, Just In Time (JIT), and Lean Accounting have an effect on net profit. Simultaneously, these three variables also have a significant effect on net profit. This implies that effective inventory management, efficient production systems through JIT, and the application of Lean Accounting can enhance a company’s financial performance. This study is expected to contribute to the development of management accounting knowledge and serve as a reference for company management in improving operational efficiency and profitability.